Human Milk Oligosaccharide Composition Is Associated With Excessive Weight Gain During Exclusive Breastfeeding—An Explorative Study - Larsson, Melanie W.; Lind, Mads V.; Laursen, Rikke Pilmann; Yonemitsu, Chloe; Larnkjær, Anni; Mølgaard, Christian; Michaelsen, Kim F.; Bode, Lars (Frontiers in Pediatrics, 2019)
Background: Some infants experience excessive weight gain during exclusive breastfeeding. The cause is unknown, but variation in human milk composition might play a role. Several human milk oligosaccharides (HMOs) have been associated with growth velocity in breastfed infants, and it has been suggested that the mechanism could be through an effect on infant gut microbiota composition. Objective: The purpose of this exploratory study was to evaluate if HMO composition was different in milk fed to infants with excessive weight gain compared to infants with normal weight gain. Furthermore, we aimed to examine if HMO composition was associated with growth velocity and change in body composition and if there were maternal determinants of HMO composition. Materials and Methods: We recruited 13 high weight-gain (HW) and 17 normal weight-gain (NW) breastfed infants, collected human milk and anthropometry data at 5 and 9 months, and analyzed HMO composition by high performance liquid chromatography. Results: In the HW group 8 out of 11 infants received milk from secretor mothers and in the NW group 15 out of 17. Comparing milk from Secretor mothers only, four HMO’s were significantly different between the HW and NW group at 5 months and two remained significant at 9 months. Total HMO concentrations as well as total HMO-bound fucose at 5 months were positively associated with both fat mass index (FMI) and weight velocity from 0-5 months (all p<0.025). 2’-fucosyllactose (2’-FL) was positively associated with weight velocity from 0-5 months and FMI at 5 months. In contrast, lacto-N-neotetraose was lower in the HW group (p=0.012) and negatively associated with height-for-age Z-scores (p=0.008), weight velocity from 0-5 months (p=0.009) and FMI (p=0.033). Maternal BMI at 5 months was negatively associated with 6’-sialyllactose and sialyl-lacto-N-tetraose (LSTb) and positively with 2’-FL, total HMO and total HMO-bound fucose (all p ≤ 0.03). Conclusion: We found significantly different HMO concentrations in milk to exclusively breastfed infants with excessive weight gain, suggesting that some HMOs, including 2’-FL, which is the most abundant HMO and currently added to some infant formula, could be part of the cause for the excessive weight gain.